Faktor Resiko Kejadian yang Menyebabkan Buta Huruf Pada Anak Sekolah di Desa Batang Bulu Baru, Kecamatan Barumun Selatan, Padang Lawas - Ummu Walidah Lubis; Bunga Lestari Hasibuan; Hasnah Angreiny; Silvana Roriska Tanjung (Universitas Batanghari Jambi, 2022)
One indicator of a country's quality of life can be determined by the Human Development Index (HDI) which is seen based on life expectancy, literacy, education, and living standards. This study aims to explain the risk factors that cause illiteracy in school children in Batang Bulu Village, South Barumun District. In this study using a descriptive method with a qualitative approach. The method of collecting data is by interviewing and observing from several communities around Batang Baru Bulu. The findings that we got in this study were that there were 5 sources we interviewed about education and illiteracy, where from these interviews we got several factors why children have the possibility of being illiterate. These factors include: teacher factors, parental factors, child factors, heredity factors, economic factors, and environmental factors. There were 3 interviewees who said that the main factor for children to be illiterate was the teacher factor, while other respondents said that the main factor was the child's parents. From these data, it will be further explained in the results and discussion of this research